#### Answer

$(3x+7)(2x-5)$

#### Work Step by Step

$6x^2-x-35$
$=6x^2-15x+14x-35$
$=3x(2x-5)+7(2x-5)$
$=(3x+7)(2x-5)$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$(3x+7)(2x-5)$

$6x^2-x-35$
$=6x^2-15x+14x-35$
$=3x(2x-5)+7(2x-5)$
$=(3x+7)(2x-5)$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.